Influence of gender roles and rising food prices on poor, pregnant women's eating and food provisioning practices in Dhaka, Bangladesh - Levay, Adrienne; Mumtaz, Zubia; Rashid, Sabina Faiz; Willows, Noreen D. (© 2013 Reproductive Health, 2017)
This article was published in the Reproductive Health [© 2013 Reproductive Health] and The Journal's website is at: https://reproductive-health-journal.biomedcentral.com/articles/10.1186/1742-4755-10-53